The influence of the family on autonomy and participation in the care of the subject diagnosed with Diabetes mellitus (Research, Society and Development, 2021)
The diagnosis of diabetes mellitus requires participation in the treatment, and changes in the lives of those who live with it, and affects not only the subject, but also his family. This study aimed to understand the influence of the family on the autonomy and participation of the care of the subject diagnosed with type 2 diabetes mellitus. This is a participatory field research, supported by the theory of reflexivity and with a qualitative approach. Sixteen subject who live with diabetes participated in meetings of a health promotion group. These participated in eight meetings for the production of data, in a closed type group, between the months of May and August of the year 2017. The results obtained showed that the factors that influence adherence to treatment are multifactorial and that they are not always directly associated with the syndrome, but also with the way people live and relate to others. Among the conclusions of the study, the support of the family of the person living with the syndrome is essential in this process, however, it was found that the participants identified negative aspects in the zeal that the family members assume in relation to the treatment. In this way, the group provided reflections on the self-care of individuals and the importance of them becoming resposible for the treatment and the search for antonomy for their lifestyles.